2016
DOI: 10.18632/oncotarget.13011
|View full text |Cite
|
Sign up to set email alerts
|

Genetic interactions between the hedgehog co-receptorsGas1andBocregulate cell proliferation during murine palatogenesis

Abstract: Abnormal regulation of Sonic hedgehog (Shh) signaling has been described in a variety of human cancers and developmental anomalies, which highlights the essential role of this signaling molecule in cell cycle regulation and embryonic development. Gas1 and Boc are membrane co-receptors for Shh, which demonstrate overlapping domains of expression in the early face. This study aims to investigate potential interactions between these co-receptors during formation of the secondary palate. Mice with targeted mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 81 publications
(138 reference statements)
0
1
0
Order By: Relevance
“…It has been suggested that SHH signaling pathway effectors may be involved in GC differentiation as well [ 19 , 20 ]. The SHH receptor Patched 1 (PTCH1), together with the co-receptors CDON (Codon), BOC (Brother of Codon), and GAS1, functions as a control switch that turns on SHH signal transduction [ 20 , 21 , 22 ]. Upon SHH binding to its receptors, PTCH1-mediated inhibition of SMO (Smoothened; a G-coupled transmembrane receptor) is lifted, allowing constitutive SMO activity and associated downstream signaling [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that SHH signaling pathway effectors may be involved in GC differentiation as well [ 19 , 20 ]. The SHH receptor Patched 1 (PTCH1), together with the co-receptors CDON (Codon), BOC (Brother of Codon), and GAS1, functions as a control switch that turns on SHH signal transduction [ 20 , 21 , 22 ]. Upon SHH binding to its receptors, PTCH1-mediated inhibition of SMO (Smoothened; a G-coupled transmembrane receptor) is lifted, allowing constitutive SMO activity and associated downstream signaling [ 23 ].…”
Section: Introductionmentioning
confidence: 99%